Magnetic resonance Adenosine perfusion imaging as Gatekeeper of invasive coronary intervention (MAGnet): study protocol for a randomized controlled trial - Buckert, Dominik (Trials, 2017)
BACKGROUND: Current guidelines for the diagnosis and management of patients with stable coronary artery disease (CAD) recommend functional stress testing for risk stratification prior to revascularization procedures. Cardiac magnetic resonance imaging (CMR) is a modality of choice for stress testing because of its capability to detect myocardial ischemia sensitively and specifically. Nevertheless, evidence from randomized trials evaluating a CMR-based management of stable CAD patients in comparison to a more common angiography-based approach still is limited. METHODS/DESIGN: Patients presenting themselves with symptoms indicating a stable CAD and a class I or IIa indication for diagnostic coronary angiography are prospectively screened and enrolled in the study. All subjects receive a basic cardiological work-up and guideline-directed medical therapy. A 1:1 randomization in two groups is being performed. Patients in group 1 undergo diagnostic coronary angiography and subsequent revascularization according to current guidelines. Subjects in group 2 undergo adenosine stress CMR and in case of myocardial ischemia are sent to coronary angiography. Follow-up is planned for 3 years. During this time, the number of primary endpoints (defined as cardiac death and non-fatal myocardial infarction) and unplanned invasive procedures will be documented. Furthermore, symptom burden and quality of life will be assessed by use of the Seattle Angina Questionnaire. Sample size is calculated to prove non-inferiority of the CMR-based approach. DISCUSSION: In case this study is able to accomplish its aim to prove non-inferiority of the CMR-based management in patients with stable CAD; the importance of this emerging modality may further increase. TRIAL REGISTRATION: ClinicalTrials.gov, identifier: NCT02580851. Registered on 14 October 2015. Unique Protocol ID: 237/11 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-017-2101-6) contains supplementary material, which is available to authorized users.